IMPACT OF FOLIAR APPLICATION OF SOME MICRNUTRIENTS NANAOFERTILIZER ON GROWTH AND YIELD OF JERUSALEM ARTICHOKE - & Saadoun, Al-juthery (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A field experiment was carried out at the fields of Al- Husseiniya District, Taliaa Township, Babylon Governorate, to study the response of the Jerusalem artichoke to foliar application of  micro nutrients nano-fertilizes of Nano Iron, Zinc, Copper ,and Manganese foliar applied at 25, 50, 75 and 100 g nano-fertilizer 100 L-1 water, and 1 kg naonfertilizers ha-1(as recommended) dissolved in  400 liters of solution ha-1.The experiment included single , di, tri and tetra combinations, as well as a tetra combination of a traditional source, in addition to control(distil water only) using RCBD with 3 replicates . Growth parameters tested were chlorophyll SPAD, dry matter yield of vegetative, tubers yield, inulin yield and % of sucrose and ascorbic acid. Results indicated that nano-applied treatment of (Cu+ Zn+ Fe+ Mn) was significantly higher followed by the triple, di and single spray combinations, in yield of fresh and dry tubers, vegetative and inulin yield giving 77.928, 19.906, 6.584 and 13. 235 Mg ha-1) ,respectively , compared with traditional fertilizers (34.320, 6.284, 3.908, and 3.345 Mg ha-1) and the control (22.655, 3.234, 3.390 and 1.201 Mg ha-1), respectively. The highest % of sucrose and ascorbic acid (vitamin c) (61.13% and 8.1%) were with tetra nano (Cu +Zn +Fe+ Mn) than other treatments.